Kaixinsan, a Well-Known Chinese Herbal Prescription, for Alzheimer's Disease and Depression: A Preclinical Systematic Review - Fu, Huan; Xu, Zhen; Zhang, Xi-le; Zheng, Guo-qing (Frontiers in Neuroscience, 2020)
Alzheimer’s disease (AD), the most common cause of dementia, is highly prevalent worldwide with no modifying therapy. Behavioral and psychological symptoms of dementia (BPSD) occur in most patients with AD, and depression is one of the most common AD-related BPSD. Kaixinsan (KXS) is an ancient Chinese herbal prescription widely used to treat dementia and forgetfulness. In this systematic review, we conducted a meta-analysis to assess preclinical evidence for the effects of KXS on cognitive impairment and depression. Thirty-eight articles involving 1050 animals were included after searching from six databases from the inception up to June 2019. The primary outcome measures were behavioral outcome. Indicators of cognitive function in AD included escape latency, time spent on the target quadrant, and the number of target platform crossings in the Morris water maze (MWM) test. Indicators of depression included number of rearing events and total distance in the open-field test, duration of immobility in the forced swim test, and sucrose consumption or sucrose preference index in the sucrose preference test. The secondary outcomes were mechanisms of KXS for treatment of AD and depression. The results showed that KXS significantly reduced escape latency (P<0.01), increased time spent in the target quadrant (P<0.01), and increased the number of target platform crossings (P<0.01) in the MWM test in AD models compared with control. The possible mechanisms for KXS-mediated improvements in cognitive function were antioxidant activity, anti-inflammatory activity, antiapoptotic activity, neuroprotection, and synapse protection. In addition, the results demonstrated that KXS significantly increased the number of rearing instances (P<0.01) and total distance (P<0.01) in the open-field test, decreased the duration of immobility (P<0.01) in forced swim test, and increased sucrose consumption or sucrose preference index (P<0.01) in the sucrose preference test in depression models compared with control. The mechanisms of KXS-mediated anti-depressive effects were HPA axis regulation, antioxidant activity, anti-inflammatory activity, synapse protection, and neuroprotection. The results of this study suggested that KXS can be used to effectively treat AD and depression through multiple mechanisms, extrapolating the therapeutic potential of KXS for treating AD-related BPSD.